Abiotic Stress Signaling and Responses in Plants - Nykiel, Małgorzata; Labudda, Mateusz; Prabucka, Beata; Gietler, Marta; Fidler, Justyna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plant responses to environmental factors are extraordinarily complex. They can be observed at various levels of plant organization, ranging from changes in the intensity of basic biochemical processes, such as respiration, photosynthesis, and transpiration, to morphological and anatomical changes in organs. However, these biochemical changes are preceded by the activation of an efficient signaling system which endures environmental fluctuations. This Special Issue showcases the latest reports on the impact of abiotic factors on plant responses. It contains 3 reviews and 9 original works and is preceded by an editorial summarizing the most important issues discussed in the publications.